The quest for ghost gear in the German Baltic Sea: A team effort between WWF, divers, fisherfolk, and public authorities - Stolte, Andrea; Dederer, Gabriele; Lamp, Jochen; Fenn, Crayton; Lee, Mareen; Frank, Wolfgang; Howe, Christian; Günther, Michael; Vesper, Heike; Werner, Stefanie (Frontiers in Marine Science, 2022)
In this pilot project, World Wild Fund for Nature (WWF) Germany works together with regional divers and fisherfolk to reduce the impact of lost fishing gear on the marine environment. If not removed, ghost gear poses a threat to seabirds, seals, harbour porpoises and fish unselectively in the Baltic Sea. Over decades to centuries, lost fishing nets and ropes shed microplastic fibres into the marine environment. Sediments and the water column can be enriched with microplastic fibres and ingested by filters feeders and bottom-dwelling fauna. Removing this hazard reduces both the risk of entanglement as well as the contamination of the marine foodweb with microplastics. After trails with different search and retrieval methodologies, WWF Germany found sonar search technology to be the most efficient technique to locate lost gear on the seafloor. The sonar technologies sound waves avoid the limitations faced by divers or visual cameras in low-visibility environments, and a substantially larger area can be covered. In contrast to diving teams focussing on wreck retrievals, the many nets lost on the seafloor remain unnoticed by divers under most circumstances. A combination of sonar search providing exact GPS positions of suspect ghost gear, diver verification, point-on retrievals with fishing vessels, and manual sorting for waste management provides an efficient methodology for long-term political implementation of regular lost gear retrieval campaigns.